Pendampingan Penerapan Digital Marekting pada Usaha Batik Rumah Batik Andalan di Kabupaten Pelalawan Untuk Peningkatan Kapasitas Produksi dan Pemasaran - Zanra, Sri Wahyuni; Kusdiana, Yayu (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This community service program aims to increase the production and marketing capacity of the Rumah Batik Andalan Batik Business in Pelalawan Regency through assistance in implementing digital marketing. The implementation method includes a participatory approach with stages of needs identification, training, intensive assistance, and evaluation of implementation results. The results of the community service program indicate that after receiving training and assistance, business owners are able to actively manage social media accounts, create engaging digital promotional content, and utilize marketplace platforms to expand their marketing network. Furthermore, there was a 35% increase in demand for batik products within two months of implementing digital marketing.